Advanced Computing and Systems for Security Volume Four - Chaki, Rituparna; Saeed, Khalid; Cortesi, Agostino; Chaki, Nabendu; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book presents extended versions of papers originally presented and discussed at the 3rd International Doctoral Symposium on Applied Computation and Security Systems (ACSS 2016) held from August 12 to 14, 2016 in Kolkata, India. The symposium was jointly organized by the AGH University of Science & Technology, Cracow, Poland; Ca' Foscari University, Venice, Italy; and the University of Calcutta, India. The book is divided into two volumes, Volumes 3 and 4, and presents dissertation works in the areas of Image Processing, Biometrics-based Authentication, Soft Computing, Data Mining, Next-Generation Networking and Network Security, Remote Healthcare, Communications, Embedded Systems, Software Engineering and Service Engineering. The first two volumes of the book published the works presented at the ACSS 2015, which was held from May 23 to 25, 2015 in Kolkata, India.
A Review on Energy Efficient Resource Management Strategies for Cloud -- Modeling and Analysis of Enterprise Cloud Bus using a Petri Net Based Approach -- Service Provisioning in Cloud : A Systematic -- Flexible Neural Trees - Parallel Learning on HPC -- Software Energy Estimation to Improve Power Efficiency of Embedded System -- Ternary Quantum Circuit for Color Image Representation -- A graph theoretic approach for visualization of data set feature association -- A Novel Approach for Human Silhouette Extraction from Video Data -- Statistical Textural features for Text-line level Handwritten Indic Script Identification -- An Approach to Stroke-based Online Handwritten Bangla Character Recognition -- Functional Group Prediction of Un-annotated Protein by Exploiting its Neighborhood Analysis in Saccharomyces Cerevisiae.
Keywords: Computational intelligence; Signal processing; Data protection; Computational Intelligence; Signal, Speech and Image Processing; Data and Information Security